The Burden and Outcomes of Abdominal Pain among Children Presenting to an Emergency Department of a Tertiary Hospital in Tanzania: A Descriptive Cohort Study. (9th May 2018) - Sakita, Francis M.; Sawe, Hendry R.; Mwafongo, Victor; Mfinanga, Juma A.; Runyon, Michael S.; Murray, Brittany L.
Abstract : Background . Abdominal pain in children can represent benign conditions or life-threatening emergencies. Aetiologies of paediatric abdominal pain vary geographically and have not been studied in acute care settings in East Africa. This study describes the clinical profiles and outcomes of children presenting with undifferentiated abdominal pain to the Emergency Department of Muhimbili National Hospital (ED-MNH). Methods . This was a prospective cohort study of children below 18 years of age presenting to the ED-MNH with abdominal pain. A structured case report form was used to collect data on patients from June to December 2016. Data included demographics, clinical presentation, and mortality. Data were summarised using descriptive statistics. Results . Out of 1855 children who presented to ED-MNH, 184 (9 . 9 %) met inclusion criteria, and all were enrolled. The median age was 3.5 years (IQR: 1.3–7.0 years) and 124 (67.4%) were male. Most (138 [75 . 0 %]) were referred from peripheral hospitals. The most frequent ED providers' diagnoses were hernia (34 [18 . 5 %]) and intra-abdominal malignancy (19 [10 . 3 %]). From the ED, 37 (20.1%) were discharged home, 83 (45.1%) were admitted to medical wards, and 48 (26.1%) were admitted to surgical wards. 16 (8.7%) underwent an operation. 24-hour, seven-day, and three-month mortality rates were 1.1%, 6.5%, and 14.5%, respectively. The overall in-hospital mortality rate was 12.2%. Multivariate analysis showed that age below 5 years, female sex, and haemoglobin less than 10.9 g/dl were significant factors associated with in-hospital mortality. Discussion and Conclusion . Abdominal pain is a common complaint among paediatric patients presenting to the ED-MNH. This presentation was associated with a high admission rate and a high mortality rate. Age below 5 years, female sex, and haemoglobin less than 10.9 g/dl were associated with mortality. Further studies and quality improvement efforts should focus on identifying aetiologies, risk stratification, and appropriate interventions to optimise patients outcomes.